European exceptionalism? - Georg Nolte; Helmut Philipp Aust (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
The paper discusses recent propositions that forms of a European exceptionalism are now emerging. The paper first asks what makes a political entity exceptionalist. For this purpose inspiration is sought in American exceptionalism as a model. The paper then discusses whether Europe displays comparable features in the fields of international legal policy and domestic rights culture. It also asks whether there are other aspects of European governance which could make it plausible to speak of a European exceptionalism. The paper concludes that it is misleading to use the term European exceptionalism because the underlying phenomena are not comparable what is usually understood as American exceptionalism.
Keywords: 320; European exceptionalism; exceptionalist; American exceptionalism